Women and Philanthropy : Boldly Shaping a Better World. - Shaw-Hardy, Sondra (John Wiley & Sons, 2010)
Based on extensive interviews and the authors' combined half-century of experience, this book shares new ways to better engage women in giving, as well as insights into helping women be more effective in their philanthropy and volunteer leadership. This book covers all of the key topics in women's philanthropy, including: the modern movement, women as prospects, how and why women give, overcoming barriers, developing gender-sensitive fundraising programs, communicating with women, women as leaders and donors, couples and family giving, and how women can and are changing philanthropy.